2003
DOI: 10.1046/j.1525-1470.2003.20507.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea Capitis Due to Trichophyton soudanense in Cincinnati, Ohio, in Internationally Adopted Children from Liberia

Abstract: Two sisters, ages 5 and 6 years, who were adopted from Liberia, presented in Cincinnati, Ohio, with tinea capitis. Fungal cultures grew Trichophyton soudanense, a dermatophyte rarely seen in North America. Both girls had multiple other infections. They responded well to therapy with oral griseofulvin and topical selenium sulfide. With the current increase in international travel and adoption, nonendemic dermatophyte infections such as this need to be recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…T. erinacei is a predominate agent in the cause of zoophilic dermatophytosis (Schauder, 2007), and in many cases treatment using normal therapies is not successful. T. soudanense is a common cause of tinea capitis in parts of Africa and West Asia, and its presence is expanding worldwide (Markey et al, 2003). T. rubrum is a predominate etiologic agent in dermatophytosis, followed by T. mentagrophytes and T. tonsurans (Foster et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…T. erinacei is a predominate agent in the cause of zoophilic dermatophytosis (Schauder, 2007), and in many cases treatment using normal therapies is not successful. T. soudanense is a common cause of tinea capitis in parts of Africa and West Asia, and its presence is expanding worldwide (Markey et al, 2003). T. rubrum is a predominate etiologic agent in dermatophytosis, followed by T. mentagrophytes and T. tonsurans (Foster et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a study from 1979 to 1981 of 54 different US locations only identified 14 of 14 696 (0.01%) tinea capitis cases that were caused by T violaceum and T soudanense . Sporadic cases have otherwise been reported intermittently since then . However, more recently, infection by T violaceum and T soudanense has increased in frequency with 25 of 1839 (1.4%) isolates identified in a series out of Baltimore, Maryland from the years 2000 to 2006 .…”
Section: Discussionmentioning
confidence: 99%
“…Published reports of T. soudanense infections in the United States have been even more infrequent. Although more recent reports describing infections in the United States due to either T. violaceum or T. soudanense are rare, Ohio investigators in 2003 described two sisters adopted from Liberia who had tinea capitis caused by T. soudanense (22).…”
Section: Discussionmentioning
confidence: 99%